Reappraising the P-T evolution of the Rogaland-Vest Agder Sector, southwestern Norway - Blereau, E.; Johnson, T.; Clark, C.; Taylor, R.; Kinny, Peter; Hand, M. (Elsevier, 2016)
© 2016 China University of Geosciences (Beijing) and Peking University.The Rogaland-Vest Agder Sector of southwestern Norway comprises high-grade metamorphic rocks intruded by voluminous plutonic bodies that include the ~1000 km2 Rogaland Igneous Complex (RIC). New petrographic observations and thermodynamic phase equilibria modelling of three metapelitic samples collected at various distances (30 km, 10 km and ~10 m) from one of the main bodies of RIC anorthosite were undertaken to assess two alternative P-T-t models for the metamorphic evolution of the area. The results are consistent with a revised two-phase evolution. Regional metamorphism followed a clockwise P-T path reaching peak conditions of ~850-950 °C and ~7-8 kbar at ~1035 Ma followed by high-temperature decompression to ~5 kbar at ~950 Ma, and resulted in extensive anatexis and melt loss to produce highly residual rocks. Subsequent emplacement of the RIC at ~930 Ma caused regional-scale contact metamorphism that affected country rocks 10 km or more from their contact with the anorthosite. This thermal overprint is expressed in the sample proximal to the anorthosite by replacement of sillimanite by coarse intergrowths of cordierite plus spinel and growth of a second generation of garnet, and in the intermediate (10 km) sample by replacement of sapphirine by coarse intergrowths of cordierite, spinel and biotite. The formation of late biotite in the intermediate sample may suggest the rocks retained small quantities of melt produced by regional metamorphism and remained at temperatures above the solidus for up to 100 Ma. Our results are more consistent with an accretionary rather than a collisional model for the Sveconorwegian Orogen.